Using Film to Elucidate Leadership Effectiveness Models: Reflection on Authentic Learning Experiences - Rajendran, Diana; Andrew, Martin (Journal of University Teaching and Learning Practice, 2014)
Abstract This paper examines how students in a third year management unit at a university of technology in Australia evaluate the usefulness of film as a tool for developing a deeper understanding of the theoretical leadership effectiveness model developed by Robbins (1997). The study reviews the range of studies describing the use of films in teaching leadership, playing into a perceivable gap in empirical studies demonstrating how students engage in applying the concepts of leadership. This study specifically considers whether films are effective interventions for achieving engagement in an assessment task aimed at identifying applications of theory to cases of leadership in action. As part of an action research cycle, thirty students (30) participated in three different focus groups. Transcriptions subsequently produced thick descriptions on which thematic analysis was conducted to extract key themes (Ryan & Bernard, 2003). The results suggest that films can communicate, embody and articulate the effectiveness of behaviours of leadership Robbins conveyed. The results also indicate that students value films as a medium for contextualising actions that demonstrate different leadership styles. It is perceived as a way of catering to diverse learning styles and as a way of building autonomy. We conclude that while films can be motivating and lend authenticity to assessment tasks, students need clear direction in making links between theoretical concepts and narrative filmic constructions of leaders and leadership behaviour. This leads to the next stage of our action research cycle.